Analisis Kemampuan Literasi Matematika Siswa dalam Menyelesaikan Soal Kontekstual pada Materi Sistem Persamaan Linea Tiga Variabel - Trapsilasiwi, Dinawati; Atmadji, Novie Kurnia Putri; Putri, Inge Wiliandani Setya; Safrida, Lela Nur; Oktavianingtyas, Ervin; Jatmiko, Dhanar Dwi Hary (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
This study aims to determine the mathematical literacy skills of tenth-grade students at MA Negeri 2 Jember in solving contextual problems related to the topic of Systems of Linear Equations in Three Variables (SPLTV).  The  contextual  problems  created  consisted  of  two  questions  covering  the  SPLTV  material.  This research is a descriptive study with a qualitative approach. The data collection method used in this study was testing. Based on the research results, it can be concluded that when the study was conducted in class X-E, the students' mathematical literacy skills were only demonstrated in the following indicators: (a) identifying real- world  situations  in  problems,  (b) representing  situations  mathematically  using  symbols,  (c) formulating problems into mathematical models, and (d) designing strategies to find solutions.